Seed Meals from Allelopathic Crops as a Potential Bio-Based Herbicide on Herbicide-Susceptible and -Resistant Biotypes of Wild Oat (Avena fatua L.) - Elżbieta Pytlarz; Dorota Gala-Czekaj (Agronomy, 2022)
Wild oat is a nuisance monocot weed mainly in cereal canopies. The increasing problem of herbicide resistance and the implementation of integrated pest management includes the use of seed meals from species with allelopathic potential. This study aimed to assess the efficacy of seed meals as an environmentally friendly alternative for the control of herbicide-susceptible (S) and -resistant (R) wild oat biotypes. A pot experiment was carried out under greenhouse conditions at the Swojczyce Research and Training Station in Wrocław (Poland) to determine the impact of seed meals from Fagopyrum esculentum, Lupinus luteus, Ornithopus sativus, Phacelia tanacetifolia, Raphanus sativus var. oleiformis and Sinapis alba at two concentrations—1 and 3%. The lowest percentage of seedling emergence was recorded after the application of S. alba seed meal. Seed meals from S. alba reduced the emergence of both S and R biotypes by approximately 82 and 61 percentage points, respectively, and limited the initial growth of both biotypes. F. esculentum, O. sativus and R. sativus seed meals generally did not decrease the number of seedlings. Almost all the seed meals inhibited the growth of the aboveground parts of the susceptible biotype of wild oat to a greater extent than the herbicide treatment.